Inflammation in Experimental Models of α‐Synucleinopathies. Issue 1 (3rd October 2020) - Harms, Ashley S.; Kordower, Jeffrey H.; Sette, Alessandro; Lindestam Arlehamn, Cecilia S.; Sulzer, David; Mach, Robert H.
ABSTRACT: Neuroinflammation has long been associated with central nervous system pathology in α‐synucleinopathy disorders including Parkinson's disease and multiple system atrophy. In the past decade, research‐focused efforts in preclinical and experimental models have rallied around this idea, and considerable effort has been made to delineate critical neuroinflammatory processes. In this article, we discuss challenges in preclinical research, notably the use of animal models to recapitulate and dissect disease phenotypes as well as the need for more sensitive, reliable radiotracers to detect on‐target efficacy of immunomodulatory treatments in both human Parkinson's disease as well as preclinical models. © 2020 International Parkinson and Movement Disorder Society